Perkembangan Kampung Adat Cireundeu: Mengoptimalkan Potensi dan Mempertahankan Keseimbangan Pada Masa Pandemi - Aldri Adha; Chantika Lutfiah; Dean Taqy; Fadlina Zaina; Widya Callista (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
Indigenous villages are villages that have a unique capacity and charm, both in terms of geography, environment, and social and cultural life in the community. The purpose of this research is to analyze the governance system in the health, economic, and environmental fields of Cireundeu Traditional Village, a Traditional Village located in South Cimahi District. Cireundeu Traditional Village was able to get through the Covid- 19 pandemic and even now Cireundeu Traditional Village is growing. There are various factors that influence the development of Cireundeu Traditional Village, there are tourism development concepts that have been applied such as management, destination development, marketing development, and the role of stakeholders that can continue to be improved to achieve maximum goals. In this research, descriptive qualitative method is used by observing in the field and conducting direct interviews with the management of Cireundeu Traditional Village. The results of this study show that Cireundeu Tourism Village can maximize the potential that exists in its territory and is able to maintain various aspects of life during the Covid-19 pandemic and is able to continue tourism activities through collaboration between stakeholders.